Global research trends in non-muscle invasive bladder cancer: Bibliometric and visualized analysis - Deng, Sheng; Meng, Fanchao; Wang, Lu; Yang, Zhen; Xuan, Lihua; Xuan, Zhihua; Wang, Jisheng (Frontiers in Oncology, 2022)
Background: Bladder cancer is one of the most common urological cancers. Non-muscle invasive bladder cancer (NMIBC) accounts for about 75-85% of all newly diagnosed bladder cancers. Globally, there are many NMIBC-related publications. However, a bibliometric analysis of these publications has not been performed. Objective: This study aims to systematically analyze and visualize NMIBC-related publications through bibliometrics, and to reveal identified topics, hotspots, and knowledge gaps in related fields. Methods: Based on the Web of Science core collection database, we firstly analyzed the quantity and quality of publications in the field of NMIBC, secondly profiled the publishing groups in terms of country, institution, author’s publication and cooperation network, and finally sorted out and summarized the hot topics of research. Results: This bibliometric analysis was conducted from 2001 to 2022. The analysis identified 2,185 articles and reviews, which were published in 402 journals. The number of publications and citations on NMIBC-related research has steadily increased over the last two decades. Furthermore, academic institutions in Europe and the United States play a leading role in NMIBC research. The country, institution, journal, and author with the most publications were the United States (559), Radboud University Nijmegen (88), Urologic oncology: Seminars and Original Investigations (141), and Witjes J (74), respectively. The most frequently used keywords were Bladder cancer (793), Recurrence (671), Urothelial carcinoma (593), Progression (523), Bacillus-calmette-guerin (411), Transitional-cell carcinoma (401), Carcinoma (366), Risk (297), Transurethral resection (286), and Non-muscle-invasive bladder cancer (280). Conclusion: More and more scholars are devoted to the research of related NMIBC. This bibliometric analysis revealed that the main research topics and hotspots in NMIBC included pathological staging, clinical diagnosis and treatment, and bladder perfusion.